Analisis Informasi Situs Web Hotel Bintang 4 di Kota Bandung - Putra, Fajar Kusnadi Kusumah (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
Four-star hotel categorized as upscale hotel where the facilities and level of services are high, a good hotel website content is very important in an online search pattern. From a hotel accommodation, tourist will get information about the hotel and for hotel side they will improve their connectivity and also interactivity with the customer. The objective of this research is to measure the level of hotel website content. In this research, samples of 38 four-star hotel websites located in the city of Bandung will be assessed by using an observation guide consists of 5 dimensions. The dimensions are: information reservation; information about the hotel facilities; contact information and the use of social media; surrounding area information; website management. Descriptive content analysis approach will be used as a tool to describe the characteristics of message content in hotel web sites and also summarize the idea of each message given. Data analysis showed that not all the hotel web site adopt indicators for good informative web site, therefore hotel are unable to provide complete information for the customer accessing related hotel websites, therefore the effect miscommunication and different perception might arise.